2020
DOI: 10.1007/s12369-020-00663-8
|View full text |Cite
|
Sign up to set email alerts
|

I, Robot: How Human Appearance and Mind Attribution Relate to the Perceived Danger of Robots

Abstract: Social robots become increasingly human-like in appearance and behaviour. However, a large body of research shows that these robots tend to elicit negative feelings of eeriness, danger, and threat. In the present study, we explored whether and how human-like appearance and mind-attribution contribute to these negative feelings and clarified possible underlying mechanisms. Participants were presented with pictures of mechanical, humanoid, and android robots, and physical anthropomorphism (Studies 1-3), attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Contrary to the results shown by (Regmi & Jones, 2020 ) in terms of e-learning, the use of other technology enhanced learning (TEL) in the health sciences field has proven to enrich and facilitate the transmission of didactic content, favoring medical training and motivating the students for example by using virtual or augmented reality (Escalada-Hernández et al, 2019 ; González Izard et al, 2020 ; Izard et al, 2018 ). However, when using robotic technology, the users’ attitudes towards robots is a major concern, as robotic appearance and behavior influences and hinders their acceptance, especially when these robots resemble human beings (Müller et al, 2020 ; Savela et al, 2018 ). This important aspect of robotic technology is considered in few of the compiled studies.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the results shown by (Regmi & Jones, 2020 ) in terms of e-learning, the use of other technology enhanced learning (TEL) in the health sciences field has proven to enrich and facilitate the transmission of didactic content, favoring medical training and motivating the students for example by using virtual or augmented reality (Escalada-Hernández et al, 2019 ; González Izard et al, 2020 ; Izard et al, 2018 ). However, when using robotic technology, the users’ attitudes towards robots is a major concern, as robotic appearance and behavior influences and hinders their acceptance, especially when these robots resemble human beings (Müller et al, 2020 ; Savela et al, 2018 ). This important aspect of robotic technology is considered in few of the compiled studies.…”
Section: Discussionmentioning
confidence: 99%
“…Human behavior, appearance, and skills are often used as a reference point when designing modern-day technology (e.g., Eyssel et al, 2012;Huang & Mutlu, 2013;Niculescu et al, 2013;Salem et al, 2011), but users do not always appreciate impressions of humanness in their machines. Indeed, several studies showed that once new technologies threaten human uniqueness, they are typically met with strong aversion (e.g., Müller et al, 2020;Złotowski et al, 2017). Even more so, social cognitive abilities such as mind-reading might play a particular role in this regard (Stein & Ohler, 2017), as our ability to infer and analyze the emotions of those around us has long served as a distinct advantage to our species (Darwin, 2009;Nesse, 1990).…”
Section: Mind Detection By Machinesmentioning
confidence: 99%
“…It is necessary for HNRs to possess abilities to express artificial emotions through linguistically appropriate and accurate communication processes, including nonverbal expressions with autonomous bodily movements. It is also critical that the appearance of HNRs would be more familiar, relatable, non-intimidating [32], does not cause human emotional unease and discomforts such as fear, anxiety, and suspiciousness, since human-like appearance of HNRs can lead to resistance [33].…”
Section: Roles and Functions Of Humanoid Nursing Partner Robotsmentioning
confidence: 99%